EQUILIBRIA OF FROG NERVE WITH DIFFERENT EXTERNAL CONCENTRATIONS OF SODIUM IONS - Lorente de Nó, R. (The Rockefeller University Press, 1951)
Using the ability of the nerve fibers to conduct impulses as indicator of changes in the concentration of sodium ions in the interstitial spaces of nerve an evaluation has been made of the diffusion constant of sodium ions. The calculated minimal value (0.62 x 10(–4) cm.(2)/min.) undoubtedly is much too low; nevertheless, it is still so high that as a rule the diffusion of sodium ions is far more rapid than the establishment of excitability changes; therefore, diffusion times need not be taken into account in the interpretation of ordinary experiments. By measurements of the changes in the longitudinal conductivity of nerve which result from changes in the external concentration of sodium chloride an evaluation has been made of the diffusion constant of sodium chloride in the interstitial spaces of nerve. A minimal value for this constant is 1.4 x 10(–4) cm.(2)/min. The evidence presented would be compatible with the assumption that the permeability of the connective tissue sheath for sodium ions decreases slightly after the concentration of sodium ions in the interstitial spaces of the nerve has become negligible; the evidence, however, shows that changes in the permeability of the sheath cannot play a significant role in determining the temporal courses of the development of inexcitability in a sodium-free medium and of the restoration of excitability by added sodium ions. If a decrease in the permeability of the sheath should take place in a sodium-free medium, the change would be small and would occur after the nerve fibers have become inexcitable; on the other hand the action of a moderate concentration of sodium ions would be sufficient to restore the permeability of the sheath. As measured by the recovery by A fibers of the ability to conduct impulses the restoration by 0.1 N sodium ions of nerve that has been deprived of sodium for 15 to 20 hours, i.e. for several hours after the nerve fibers have become inexcitable, begins after a significant delay, since no A fiber begins to conduct impulses in less than 8 or 10 minutes. The delay is referable to the fact that, before the A fibers can regain the ability to conduct impulses, those changes in their properties have to be reversed, which have taken place in the absence of sodium ions. Usually within 1 minute after sodium ions are made available to the nerve the polarizability of the membrane by the anodal current begins to increase; the A fibers soon begin to produce unconducted impulses in response to the break of the anodal current; then, they produce unconducted impulses in response to the closure of the cathodal current, and finally they become able to conduct impulses, although at a markedly reduced speed. The C fibers, that become inexcitable in a sodium-free medium later than the A fibers, begin to conduct impulses within 1 minute or 2 after 0.1 N sodium ions are made available to the nerve. Treatment of a nerve, that has been kept in a sodium-free medium, for 15 to 20 hours, with a moderate concentration of sodium ions (0.015, 0.02 N), acting for 1 hour or 2, is not sufficient to restore the ability to conduct impulses to more than a few A fibers, but it produces in a relatively large number of fibers a partial restoration, so that when the concentration of sodium ions outside the epineurium is increased by 0.005 or 0.01 N a significant number of A fibers begin to conduct impulses within less than 5 seconds. Initially the recovery progresses with great rapidity, but after a small number of minutes the height of the conducted spike remains practically stationary. Increase of the external concentration of sodium ions by a small amount again causes a rapid enhancement of the recovery, but once more, after a few minutes the height of the spike remains practically stationary, etc. A subnormal concentration of sodium ions may restore to all the A fibers the ability to conduct impulses, but only 0.1 N sodium ions are able to produce a complete restoration of the speed of conduction, and only after they have been allowed to act for a considerable period of time. The ability of all the C fibers to conduct impulses may be restored by relatively small concentrations of sodium ions, 0.02 to 0.025 N. Nerve fibers that have become inexcitable in a sodium-free medium and have been restored by sodium ions are far more sensitive to the effect of the lack of sodium than the fibers of untreated nerve. Repeated removal and addition of sodium ions may bring the nerve fibers, especially those of spinal roots, to a state in which the sensitivity to the lack of sodium is exceedingly great; spinal root fibers may then begin to become inexcitable in a sodium-free medium within a few seconds. Treatment of the nerve with 0.1 N sodium ions for 1 hour or 2 is sufficient to bring about a marked increase in the resistance to the lack of sodium. On the other hand keeping a nerve in Ringer's solution or in the presence of 0.04 N sodium ions does not produce a readily detectable increase in the sensitivity to the lack of sodium. Even the resistance of nerve kept in the presence of 0.025 N sodium ions for 23 hours is very high, since after 2 hours in a sodium-free medium more than two-thirds of the initially conducting fibers will be able to conduct impulses. Frog nerve reaches different states of equilibrium with different external concentrations of sodium ions. The states are characterized by the degree of effectiveness of the nerve reaction, the speed of conduction of impulses, and the number of conducting fibers. Approximately the same equilibrium state may be reached by (a) leaving the nerve for 20 to 24 hours in the presence of a subnormal concentration of sodium ions and (b) by leaving the nerve in a sodium-free medium for 15 to 20 hours, restoring it with 0.1 N sodium ions acting for a short period of time, rendering it inexcitable again in a sodium-free medium, and finally restoring it with a moderate concentration of sodium ions. If, however, the nerve that has been kept in a sodium-free medium for 15 to 20 hours is restored directly by a moderate concentration of sodium ions the state will not be reached, at least not for several hours, which corresponds to equilibrium with that concentration. The role of sodium in nerve physiology is discussed. Sodium participates in at least four processes, (a) The regulation of the concentration of water outside the nerve fibers; (b) the regulation of the total value of the membrane potential; (c) the production of the nerve impulse, and (d) the establishment of the nerve reaction. In so far as processes (c) and (d) are concerned only the sodium present inside the nerve fibers plays a role; the presence of sodium ions outside the nerve fibers is important only because in the absence of interstitial sodium ions the nerve fibers lose a part of their internal sodium content. The nerve impulse and the nerve reaction may be produced for long periods of time after the concentration of sodium ions outside the nerve fibers has become negligible. A working hypothesis is put forward according to which the internal sodium content and the interstitial concentration of sodium ions are in equilibrium in so far as a different internal sodium content corresponds to each interstitial concentration. The properties of the nerve fibers are determined by the internal sodium content. The change in properties, i.e. in the state of the nerve fibers, results from processes that take place inside the nerve fibers after the interstitial concentration of sodium ions and consequently also the internal sodium content have been changed.